The Disenfranchisement of Voters of Color: Redux. (4th March 2021) - Portillo, Shannon; Bearfield, Domonic; Riccucci, Norma M.
Abstract : This article unpacks how voters of color continue to be disenfranchised by policy and administrative action. In 2013, the US Supreme Court issued a decision in Shelby County v. Holder, which struck down key provisions of the Voting Rights Act of 1965. This ruling sets the stage for states to change their election laws which have perpetuated voter suppression and the disenfranchisement of people of color and low-income whites. The article examines the practices and policies across the states, with a focus on the role of public administrators. Current election policies in a number of states force administrators to confront the challenges of promoting values of efficiency and effectiveness with the normative values of equity and fairness. While public administrators have an obligation to be non-partisan, there must be a focus on access and equity that extends to the ballot box.